Clinical characteristics of full thickness macular holes that closed without surgery. Issue 10 (29th April 2021) - Uwaydat, Sami H; Mansour, Ahmad; Ascaso, Francisco J; Parodi, Maurizio Battaglia; Foster, Robert; Smiddy, William E; Schwartz, Stephen G; Charbaji, Abdulrazzak; Belotto, Silvana; Jürgens, Ignasi; Mateo, Javier; Ellabban, Abdallah A; et al.
Abstract : Purpose: To ascertain the anatomic factors that help achieve non-surgical sealing in full thickness macular hole (FTMH). Methods: Retrospective collaborative study of FTMH that closed without surgical intervention. Results: A total of 78 patients (mean age 57.9 years) included 18 patients with blunt ocular trauma, 18 patients that received topical or intravitreal therapies and 42 patients with idiopathic FTMH. Mean±SD of the initial corrected visual acuity (VA) in logMAR improved from 0.65±0.54 to 0.34±0.45 (p<0.001) at a mean follow-up of 33.8±37.1 months. FTMH reopened in seven eyes (9.0%) after a mean of 8.6 months. Vitreomacular traction was noted in 12 eyes (15.8%), perifoveal posterior vitreous detachment in 42 (53.8%), foveal epiretinal membrane in 10 (12.8%), cystoid macular oedema (CME) in 49 (62.8%) and subretinal fluid (SRF) in 20 (25.6%). By multivariate analysis, initial VA correlated to the height (p<0.001) and narrowest diameter of the hole (p<0.001) while final VA correlated to the basal diameter (p<0.001). Time for closure of FTMH (median 2.8 months) correlated to the narrowest diameter (p<0.001) and the presence of SRF (p=0.001). Mean time for closure (in months) was 1.6 for eyes with trauma, 4.3 for eyes without trauma but with therapy for CME, 4.4 for eyes without trauma and without therapy in less than 200 µm in size and 24.7 for more than 200 µm. Conclusion: Our data suggest an observation period in new onset FTMH for non-surgical closure, in the setting of trauma, treatment of CME and size <200 µm.